Vertical IS standards deployment and integration : a study of antecedents and benefits - Xu, Yun (2014)
We drew on institutional and learning theories to develop a research model assessing how organizations influence standards deployment and integration by creating institutional pressures and learning opportunities. We also examined how standards deployment and integration differentially influenced operational and strategic benefits. Survey data was collected from organizations in China who have implemented RosettaNet. Overall, the study extended research on standards adoption by examining how the learning perspective complemented institutional pressures, generating an integrated view of how pressures and learning from other organizations influence standards deployment and integration as important dimensions of standards use, as well as the benefits arising from their use.